PENGEMBANGAN MEDIA UNPLUGGED COKIS ( CODING MAKANAN BERGIZI DAN SEHAT ) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS ANAK USIA DINI - Felysa Amalia Bahti; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi; Sri Widayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop the Unplugged COKIS (Coding Nutritious and Healthy Food) learning media to improve critical thinking skills in early childhood. The background of this research is based on children's low critical thinking skills, demonstrated by difficulties in identifying problems, analyzing information, making decisions, and justifying choices. Therefore, innovative learning media is needed that is interactive, contextual, and appropriate to the characteristics of early childhood. The COKIS media was developed by integrating the concept of unplugged coding and material on nutritious and healthy food through an educational game approach. This research used a Research and Development (R&D) method with stages of planning, development, validation, and limited trials. The research subjects were children aged 5–6 years. Data collection techniques included expert validation sheets, observation sheets, and critical thinking assessment instruments. Data analysis was conducted to determine the level of validity and practicality of the developed media.The results showed that the Unplugged COKIS media had a high level of validity based on assessments by material experts and media experts, and was deemed practical for use in learning activities. This media can stimulate indicators of children's critical thinking, such as the ability to analyze information, observe, and provide reasons in problem-solving. Therefore, Unplugged COKIS media is a suitable learning alternative to improve critical thinking skills in early childhood while also instilling an understanding of the importance of nutritious and healthy food.